DESKRIPSI KETERAMPILAN MEMBACA SISWA KELAS AWAL DI SEKOLAH DASAR INKLUSIF - Dira Annisa; Haifaturrahmah; Yuni Mariyati (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
Inclusive education aims to provide equal opportunities for all students, yet challenges persist in foundational skills, particularly reading literacy. This descriptive qualitative study aimed to comprehensively describe the reading skills of early-grade students (Grades I–III) and the adaptive strategies implemented by teachers at SDN 20 Mataram. Data were collected through structured observation, in-depth interviews with Class Teachers and Special Assistant Teachers (GPK), and documentation. The findings, based on purposive sampling, show a heterogeneous distribution of reading skills, with a significant 30% of students categorized as Not Yet Fluent, comprising Students with Special Needs (PDBK) and regular students facing specific learning difficulties. This group primarily struggles with technical fluency, low motivation, and difficulties in phoneme grapheme association. Teachers address this gap through differentiated practices, implementing (1) Individual Learning Programs (PPI) for PDBK, (2) Multisensory and Planned Repetition Strategies to enhance technical skills, and (3) flexible classroom management, including strategic student placement. The study concludes that successful literacy development in inclusive settings is highly dependent on continuous collaboration between class teachers and GPK in designing responsive and adaptive pedagogical strategies. The implications of this research suggest that the descriptive insights into students’ reading skills and teachers’ adaptive strategies can serve as an empirical foundation for developing more effective and sustainable literacy intervention models in inclusive elementary schools